EFFECT OF GAMMA RADIATION AND ETHYL METHANESULFONATE (EMS) ON POTATO SALT STRESS TOLERANCE IN VITRO - & Abdulrasool, Annon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
An experiment was conducted in the Date Palm Research Units labs / College of Agricultural Engineering Sciences / University of Baghdad to assess the tolerance toward salinity stress in potato after two mutagens treatments in vitro. Potato cv. Arizona and Rivera nodal segments were irradiated with four dosages of gamma rays at 0, 10, 20, and 30 Gray and immersed in (EMS) with four concentrations included 0, 10, 20, and 30 mM. The survival rates after mutagenesis treatments were calculated and 449 lines were obtained. The lines were tested for salinity tolerance by growing in MS medium supplemented with four concentrations of NaCl at 0, 100, 150, and 200 mM and data were analyzed according to the CRD with 10 replicates and means were compared according to LSD at 5%. Out of 449 lines obtained, only 38 lines were showed to be tolerant to salinity stress depending on some vegetative characteristics. At the highest NaCl concentration of 200 mM, Almost all derived lines were higher when compared with their controls especially the lines that derived from Arizona in which line 262 gave the most significant plantlets height of 35 mm and line 180 gave the most significant number of nodes of 3.66 nodes.plant-1 and number of shoots of 2 shoots.plant-1 when compared with their control that gave 11.33 mm, 2 nodes.plant-1, and 1.5 shoots.plant-1, respectively. The resulted lines were analyzed at the molecular level utilizing the inter simple sequence repeats (ISSR) markers and revealed that line 69 was the much distanced from its derived Rivera cultivar while lines 551, 261, 170, 262, 459, 463 were the much genetically distanced from their derived cultivar Arizona.